Sustainable customer relationship management for BIM procurement in the ornamental stones cluster under industry 4.0 - Razy, A.; Mirnoori, S.; Silva, J.; Silva, A.; Möhring, M.; I. Almeida (Proceedings of 26th EurOMA – Operations adding value to society, 2019)
The construction industry competitive environment has been demanding buildings conforming with the dynamic customer/owner requirements put together with the procurement of adequate personalised natural materials made to order in integrated value networks. But, the technological push has introduced BIM procurement as a mandatory industry best practice that demands standard mass produced materials (made to stock) to be introduced in IFC e-libraries ahead of their selection by technical specialists, not the owner. A three experts focus group generated an innovative Cyber Physical System conceptual model (research contribution) to solve this apparent paradox arising from an in depth literature review (theoretical contribution).